Nonautoimmune Hyperthyroidism Caused by a Somatic Mosaic GNAS Mutation Involving Part of the Thyroid Gland - França, Monica M. (Thyroid, 2020)
Nonautoimmune hyperthyroidism caused by activating mutations in the GNAS gene is a rare condition. In this study, we report a five-year-old girl diagnosed with nonautoimmune hyperthyroidism and tall stature harboring a somatic mosaic gain-of-function mutation in the GNAS gene (NM_080425.3: c.2530C>T;p.Arg844Cys previously reported as NM_000516.5:c.601C>T;p.Arg201Cys) and referred to thereafter as R201C, in three of four quadrants of the thyroid gland. Provision of a molecular diagnosis may avoid unnecessary complete ablation of the thyroid gland.